Immunological Responses and Protection in the Largemouth Bass (Microterus salmoides) Immunized with Inactivated Vaccine Against Largemouth Bass Ranavirus (LMBRaV) - Tao Yang; Jiale Zhai; Chenyang Li; Lingbing Zeng; Yiqun Li; Wenzhi Liu; Yan Meng; Yuding Fan; Zhenyu Huang; Yong Zhou; Nan Jiang (Animals)
The largemouth bass ranavirus (LMBRaV) caused significant mortality and economic loss in the largemouth bass aquaculture industry around the world, including China. Vaccination is an efficient method for virus defense. In this study, an inactivated LMBRaV vaccine was prepared, and the prevention effect as well as the immune responses were analyzed after the primary and the secondary immunization. Compared to the control group, the counts of leucocytes and erythrocytes increased and peaked at day 14 after the primary immunization, and the proportions of leucocytes, including lymphocytes, monocytes, and neutrophils, were also up-regulation after the primary immunization. Serum neutralizing antibody titers increased and peaked (1:128) at day 28 after the primary immunization. Following the secondary immunization, antibody titers were increased to a higher level (1:512) at 28 days after the secondary immunization. Quantitative real-time PCR analysis demonstrated varying degrees of up-regulation of mhc II, igM, il-1β, and cd8α transcriptions in the head kidney, which showed that innate and adaptive immune responses were both induced after the primary and the secondary immunization. After challenge with LMBRaV, the relative percent survival rates (RPS) for primary and secondary immunization with inactivated LMBRaV vaccine were determined to be 62.92% and 95.51%, respectively. Therefore, this study suggests that utilizing an inactivated LMBRaV vaccine could induce efficient immune responses and antibody, which might provide a potential efficient countermeasure for LMBRaV prevention.